Load-settlement Behavior of Steel Piles in Different Sandy Soil Configurations (Journal of Engineering, 2020)
In the case where a shallow foundation does not satisfy with design requirements alone, the addition of a pile may be suitable to improve the performance of the foundation design. The lack of in-situ data and the complexity of the issues caused by lagging in the research area of pile foundations are notable. In this study, different types of piles were used under the same geometric conditions to determine the load-settlement relationships with various sandy soil relative densities. The ultimate pile capacity for each selected pile is obtained from a modified California Bearing Ratio (CBR) machine to be suitable for axial pile loading. Based on the results, the values of Qu for close-ended square pile were increased by 15.2, 19.3, and 9.1 % for different pile lengths of 100, 150, and 200 mm in comparison with the H-pile. At the same time, the open-ended square pile had a lower capacity in comparison with closed-ended square pile tested in medium sand. Also, in the dense sand, the values of Qu for close-ended square pile were increased by 49.7, 47.8, and 69.6% for the same pile length in comparison with the H-pile. Notably, sand's density has a significant effect on the ultimate load capacity for different types of piles.